2005
DOI: 10.1016/j.polymer.2005.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A unified approach to conformational statistics of classical polymer and polypeptide models

Abstract: We present a unified method to generate conformational statistics which can be applied to any of the classical discrete-chain polymer models. The proposed method employs the concepts of Fourier transform and generalized convolution for the group of rigid-body motions in order to obtain probability density functions of chain end-to-end distance. In this paper, we demonstrate the proposed method with three different cases: the freely-rotating model, independent energy model, and interdependent pairwise energy mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…If the frames of reference g i and g i +1 are attached at the C α atoms of residues i and i + 1 in a polypeptide, then the function f i,i +1 ( g i,i +1 ) would be the six-dimensional generalization of a Ramachandran map that could include small bond angle bending, warping of the peptide plane and even bond stretching. If one chooses not to model these effects, then the classical Ramachandran map [64] can be reflected by appropriately defining f i,i +1 ( g i,i +1 ), as has been done in [44]. This is consistent with the Flory isolated pair model [33], which has been challenged in recent years [61].…”
Section: Computing Bounds On the Entropy Of The Unfolded Ensemblementioning
confidence: 85%
See 1 more Smart Citation
“…If the frames of reference g i and g i +1 are attached at the C α atoms of residues i and i + 1 in a polypeptide, then the function f i,i +1 ( g i,i +1 ) would be the six-dimensional generalization of a Ramachandran map that could include small bond angle bending, warping of the peptide plane and even bond stretching. If one chooses not to model these effects, then the classical Ramachandran map [64] can be reflected by appropriately defining f i,i +1 ( g i,i +1 ), as has been done in [44]. This is consistent with the Flory isolated pair model [33], which has been challenged in recent years [61].…”
Section: Computing Bounds On the Entropy Of The Unfolded Ensemblementioning
confidence: 85%
“…The case of statistical distributions when semi-flexible polymers have internal joints and rigid bends has also been addressed using these methods [87, 88]. And it has been shown that this method can be applied to more general polymers including unfolded polypeptide chains [44]. Similar tools can be used to analyze large amounts of geometric data in the protein data bank [5] such as statistics of helix-helix crossing angle [50] and the relative pose (position and orientation) between alpha carbons in proteins [14, 49].…”
Section: Introductionmentioning
confidence: 99%
“…Similar problems arise in the study of chainlike biological macromolecules that undergo thermal fluctuations in solution. See, for example, Zhou and Chirikjian (2006) and Kim and Chirikjian (2005). As another example, consider a non-holonomic mobile robot that executes an open loop trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…This has been applied to polymer chains. 45,46 One of the most popular methods for numerical inverse kinematics relies on Jacobian iterations to update joint angles. Many variations on Jacobian-based iterative methods for solving serial chain inverse kinematics problems have been proposed in the literature.…”
Section: An Inverse Kinematic Solution Using the Jacobianmentioning
confidence: 99%